Hepatitis C Virus in Pregnancy - Prasad, Mona R.; Honegger, Jonathan R. (American Journal of Perinatology, 2013)
Despite recent advances in the pathogenesis, treatment, and public health response to hepatitis C virus (HCV), HCV as it specifically relates to pregnancy has been a neglected condition. HCV-monoinfected pregnant women have a 2-8% risk of viral transmission to their infant, but the mechanism and timing of mother to child transmission (MTCT) are not fully understood, nor is the natural history of the illness in pregnant women and their offspring. Recognition of HCV-infected pregnant women is relevant because of the long-term health implications for the mother, potential adverse effects of infection on pregnancy outcomes, and the possibility of transmission to their infants. Certain risk factors for MTCT of HCV appear similar to those for human immunodeficiency virus (HIV); however, unlike HIV, effective methods for prevention of HCV vertical transmission have not been developed. It is possible that a better understanding of HCV MTCT and pathogenesis in pregnancy will guide development of useful prevention strategies, particularly as we enter an era where interferon-free drug cocktails may emerge as viable treatment options for HCV.
Keywords: hepatitis C virus (HCV); pregnancy; mother to child transmission; screening